A RARE MASSIVE CERVICAL FIBROMA IN A BUFFALO - UMAMAGESWARI, J; DAS, ANANGA KUMAR; BALASUBRAMANIAN, S; KRISHNAKUMAR, K; MOHAN, P; ARUNMOZHI, N (The Indian Journal of Animal Reproduction, 2015)
A rare case of massive cervical fibroma in a buffalo is presented and discussed.